Intervention-related factors associated with physical activity maintenance among post-stroke patients: a protocol for a systematic review with meta-analysis and meta-regression. Issue 8 (5th August 2020) - Masrur, Muhib; Richardson, Julie; Tang, Ada; Thabane, Lehana; Cino, Emily
ABSTRACT: Objective: The aim of this review is to i) evaluate the effectiveness of current rehabilitation interventions in promoting short-, moderate-, and long-term physical activity maintenance among patients post-stroke, and ii) to investigate the intervention characteristics associated with the promotion of physical activity maintenance among patients post-stroke. Introduction: Physical activity and exercise can positively impact post-stroke recovery. However, few patients participate in the recommended levels of physical activity after a stroke. To design better post-stroke programs, the characteristics of current interventions that promote physical activity maintenance need to be identified. Inclusion criteria: Randomized controlled trials including adults (age ≥ 18) post-stroke, assessing physical activity via subjective or objective measures with a minimum three-month follow-up, and published in English will be considered for inclusion. Methods: Literature searches will be conducted using MEDLINE, Embase, PsycINFO, CINAHL, SPORTDiscus, and Cochrane Central Register of Controlled Trials. The quality of the randomized controlled trials will be assessed using Cochrane's risk of bias tool. Interventions will be coded using the Behaviour Change Technique Taxonomy version 1. Standardized mean differences of physical activity levels between intervention and control groups will be calculated using study-specific measures and interpreted as small (<0.40), medium (0.40–0.70), or large (>0.70). Meta-analysis of effect sizes will be conducted for short- (three months), moderate- (six months), and long-term (≥12 months) follow-ups. Univariable and multivariable random effects meta-regression using intervention characteristics (setting, delivery method, delivery type, duration, outcome measure, and behavior change techniques) will be conducted to identify predictors of maintenance. Systematic review registration number: PROSPERO CRD42019131056